Diary of a wimpy kid : the ugly truth - Kinney, Jeff. (London : Puffin Books, 2010)
While trying to find a new best friend after feuding with Rowley, middle-school slacker Greg Heffley is warned by older family members that adolescence is a time to act more responsibly and to think seriously about his future.
5.6
5-8
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Maturation (Psychology) -- Juvenile fiction; Diaries -- Fiction; Family life -- Fiction; Friendship -- Fiction; Humorous stories; Maturation (Psychology) -- Fiction; Diaries -- Fiction; Family life -- Fiction; Friendship -- Fiction; Humorous fiction; Maturation (Psychology) -- Fiction; Diary fiction; Humorous fiction